Seeing is believing: The effect of brain images on judgments of scientific reasoning - McCabe, David P.; Castel, Alan D. (Cognition, 2008)
Brain images are believed to have a particularly persuasive influence on the public perception of research on cognition. Three experiments are reported showing that presenting brain images with articles summarizing cognitive neuroscience research resulted in higher ratings of scientific reasoning for arguments made in those articles, as compared to articles accompanied by bar graphs, a topographical map of brain activation, or no image. These data lend support to the notion that part of the fascination, and the credibility, of brain imaging research lies in the persuasive power of the actual brain images themselves. We argue that brain images are influential because they provide a physical basis for abstract cognitive processes, appealing to people’s affinity for reductionistic explanations of cognitive phenomena.
Keywords: Brain imaging; Cognitive neuroscience; Persuasion; Scientific communication; fMRI